Chapter Auditory Verbal Hallucinations and Inner Speech A Predictive Processing Perspective - Wilkinson, Sam (Imprint Academic, 2017)
Inner speech is a pervasive feature of our conscious lives.1 But what is inner speech, and what happens in unconscious processing that makes it the conscious experience that it is? A clue to answering this can be found in cases where the mechanisms that produce inner speaking behave unusually. In this paper, we suggest an account of a specific instance of this, namely, a particular subtype of auditory verbal hallucination (AVH), and draw some lessons about the processes that underlie normal inner speech.